2022
DOI: 10.1101/2022.05.30.493983
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Monocyte-derived macrophages aggravate pulmonary vasculitis via cGAS/STING/IFN-mediated nucleic acid sensing

Abstract: Autoimmune vasculitis is a group of life-threatening diseases, whose underlying pathogenic mechanisms are incompletely understood, hampering development of targeted therapies. Here, we demonstrate that patients suffering from anti-neutrophil cytoplasmic antibodies (ANCA)-associated vasculitis (AAV) showed increased activity of the DNA sensor cGAS and enhanced IFN-I signature. To identify potential therapeutic targets, we developed a mouse model for pulmonary AAV that mimics severe disease in patients. Immunoge… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Indeed, monocytic infiltrate has been observed, and it is conceivable that they could be composed of the disease-associated monocytes identified in the blood. The role of monocytes and monocytederived macrophages is increasingly recognized in pulmonary fibrosis [50][51][52][53] . Additionally, the integrated stress response, a strongly induced pathway in these monocytes, has also been proposed as an important driver of pulmonary fibrosis 54 , which further supports the hypothesis that the disease-associated monocytes may drive the pulmonary damage in SAVI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, monocytic infiltrate has been observed, and it is conceivable that they could be composed of the disease-associated monocytes identified in the blood. The role of monocytes and monocytederived macrophages is increasingly recognized in pulmonary fibrosis [50][51][52][53] . Additionally, the integrated stress response, a strongly induced pathway in these monocytes, has also been proposed as an important driver of pulmonary fibrosis 54 , which further supports the hypothesis that the disease-associated monocytes may drive the pulmonary damage in SAVI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Vibratome sections of lungs 2 days after infection were analysed as previously described [9]. Briefly, mice were humanely killed by xylazine/ ketamine overdose and lungs inflated with 1 ml of 2% low melting temperature agarose (Promega, US) at 37 °C.…”
Section: Confocal Microscopymentioning
confidence: 99%
“…However, another study found that inducing macrophage apoptosis resulted in an decreased burden of L. pneumophila and L. longbeachae in the lungs of mice [7]. In addition, monocytes that infiltrate the lung after infection and their progeny such as AM-like cells, inflammatory macrophages, and dendritic cells [8][9][10][11], have been shown to be important mediators of defence against L. pneumophila and L. longbeachae [12]. Whereas it is known that monocyte-derived cells (MC) protect against L. pneumophila via production of pro-inflammatory interleukin (IL)-12 [10,12], the mechanisms of protection against L. longbeachae are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…As part of the innate immune system, the cGAS-STING pathway forms a critical surveillance system that responds to widespread tissue damage and pathogen invasions. Its dysregulation is linked with the pathogenesis of a broad range of human diseases, including infectious diseases, autoimmune diseases, cancer, and neurodegenerative diseases (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%